The Contexts of Academic Pressure: Narrative Review - Qomariyah, Laili; Ekowati, Dian; Mudzakkir, Mohammad Fakhruddin (RSF Conference Series: Business, Management and Social Sciences, 2023)
Academic pressure is the pressure experienced by individuals related to academics. There are many contexts of academic pressure resulting from previous studies. The purpose of this research is to comprehensively explore and analyze the causes and impacts of academic pressure in many contexts. This research is important to do because currently there are increasing demands from an academic that must be understood by stakeholders to mitigate the emergence of negative impacts. The researcher conducted an article search using the keyword "academic pressure". Apart from keywords, researchers limit articles to English only. The article search was conducted on June 21 2023, and is limited to the year of publication between 2012 and 2023. The articles are articles sourced from the Scopus and Google Scholar databases. Researcher used narrative synthesis to summarize the evidence. The results of the review show that academic pressure has two major contexts, namely, students and lecturers. The antecedents and consequences of academic pressure on students and lecturers have also been discussed. A review of academic pressure can be a valuable contribution to stakeholders in determining and providing academic targets for students and lecturers. In addition, the results of this review of academic pressure can be a trigger for other researchers to study academic pressure in more depth related to the dimensions of academic pressure.